EMPOWERMENT IN EVALUATION: CUSTOMIZING ASSESSMENTS FOR SENIOR HIGH SCHOOL WITH AN EMANCIPATED CURRICULUM APPROACH - Amalia, Veninda Ayu; Kerti Nitiasih, Putu; Mahayanti, N.W. Surya (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2024)
This study aimed to develop differentiated instruments assessment for 10th-grade students in Senior High School. The D&D method by Richey & Klein (2008) served as the research design, supported by ADDE procedures. Two teachers from two different schools were recruited as informants for the study. Data were collected through ADDE procedures, including observation, interviews, document analysis, and questionnaires. The collected data were analyzed using a qualitative approach by Miles, Huberman, & Saldaña (2014), starting with data reduction, data display, and drawing conclusions, and quantitatively using Nurkancana and Sunartana’s (1992) Formula. The findings showed that teachers greatly needed differentiated instruments assessment for 10th-grade students in Senior High School. It was found from the statements of L1 and L2 that they did not yet have differentiated assessment forms despite differentiating during diagnostic assessment. The lack of alignment between the results of diagnostic assessment and the assessment process at the end of learning prevented the achievement of assessment goals. This also included issues with the structure and implementation plan of the assessment